A Framework for Revisiting Brain Death: Evaluating Awareness and Attitudes Toward the Neuroscientific and Ethical Debate Around the American Academy of Neurology Brain Death Criteria. (October 2021) - Chatterjee, Krishanu; Rady, Mohamed Y.; Verheijde, Joseph L.; Butterfield, Richard J.
Background: There remains a lack of awareness around the American Academy of Neurology (AAN) procedural criteria for brain death and the surrounding controversies, leading to significant practice variability. This survey study assessed for existing knowledge and attitude among healthcare professionals regarding procedural criteria and potential change after an educational intervention. Methods: Healthcare professionals with increased exposure to brain injury at Mayo Clinic hospitals in Arizona and Florida were invited to complete an online survey consisting of 2 iterations of a 14-item questionnaire, taken before and after a 30-minute video educational intervention. The questionnaire gathered participants' opinion of (1) their knowledge of the AAN procedural criteria, (2) whether these criteria determine complete, irreversible cessation of brain function, and (3) on what concept of death they base the equivalence of brain death to biological death. Results: Of the 928 people contacted, a total of 118 and 62 participants completed the pre-intervention and post-intervention questionnaire, respectively. The results show broad, unchanging support for the concept of brain death (86.8%) and that current criteria constitute best practice. While 64.9% agree further that the loss of consciousness and spontaneous breathing is sufficient for death, contradictorily, 37.6% believe the loss of additional integrated bodily functions such as fighting infection is necessary for death. A plurality trusts these criteria to demonstrate loss of brain function that is irreversible (67.6%) and complete (43.6%) at baseline, but there is significantly less agreement on both at post-intervention. Conclusion: Although there is consistent support that AAN procedural criteria are best for clinical practice, results show a tenuous belief that these criteria determine irreversible and complete loss of all brain function. Despite support for the concept of brain death first developed by the President's Council, participants demonstrate confusion over whether the loss of consciousness and spontaneous breath are truly sufficient for death.